How Does Herbal Medicine Treat Idiopathic Membranous Nephropathy? - Feng, Zhendong; Liu, Wenbin; Jiang, Han Xue; Dai, Haoran; Gao, Chang; Dong, Zhaocheng; Gao, Yu; Liu, Fei; Zhang, Zihan; Zhao, Qihan; Zhang, Lei; Liu, Baoli (Frontiers in Pharmacology, 2020)
Idiopathic membranous nephropathy (IMN) has made increasing progress in mechanism and treatment research. Herbal medicine is gradually being accepted as an alternative therapy in treating IMN. However, the intervention mechanism of herbal medicine in the treatment of membranous nephropathy is still unclear. In this review, we summarize some achievements of herb medicine in treating IMN and discuss the research direction of herb in IMN. Finally, we propose the dilemma about the study on the treatment of IMN with herb medicine. We hope that this article can bring some thoughts for clinical and scientific researchers on the treatment of IMN with herb medicine.